EARLY OPERATIVE MANAGEMENT OF COMPLICATED APPENDICITIS IS ASSOCIATED WITH IMPROVED SURGICAL OUTCOMES IN ADULTS: A SYSTEMATIC REVIEW - Hekmatyar, Mohamad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Appendectomy is one of the most common surgeries in the US, with over 300,000 performed annually. In addition, 20% of adults may have complex appendicitis with extensive peritonitis, perforation, abscess, or phlegmon. In severe appendicitis patients, there is no unanimity on whether to operate or when. Statistics contradict each other. Non-operative care and radiologically guided percutaneous drainage have become prominent treatments. The aim: This article demonstrated an association between early surgical management of complicated appendicitis and enhanced surgical outcomes in adults. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 68 articles, whereas the results of our search on SagePub brought up 51 articles. The results of the search conducted for the last year of 2013 yielded a total 19 articles for PubMed and 13 articles for SagePub. In the end, we compiled a total of 11 papers, 7 of which came from PubMed and 4 of which came from SagePub. We included three study that met the criteria. Conclusion: The benefits of immediate surgery for patients with complicated appendicitis include a reduction in hospitalization time, subsequent infections, and short-term mortality, according to research.